Effective microorganisms formulation in enhancing rice productivity / Nur Ajlaa Mohd Ngalim - Mohd Ngalim, Nur Ajlaa (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa L) is one of the most essential staple foods in the world as it is become one of the world's population diet. In order to reduce the application of chemical fertilizer, Effective Microorganisms (EM) has been applied in this study. The study used Trichoderma koningii as the main ingredient in the EM because this type of fungi has been proven by researcher to increase rice plants height, root length, wet weight, leaf number and biomass compared to untreated rice plants (control). The experiment was carried out in the greenhouse of UiTM Jasin and Mycology Laboratory in complete randomized design (CRD) based on four treatments and four replications. The variety of rice used was MR219 that obtained from Malaysian Agricultural Research and Development Institute (MARDI) and the treatments were 100ml, 300ml and 500ml of EM. The EM formulation have benefits on all measured parameters such as plant height, number of tillers and grains weight. The maximum plant growth was noted in plant treated with 500ml of EM that represents the excellent of growth performance of rice with the highest mean value of number of grains per panicle (114.25 + 83.292). Hence, from this study the treatment of effective microorganisms combine with T. koningii fungi was proved in enhancing the rice productivity.